2002
DOI: 10.1097/00002820-200204000-00003
|View full text |Cite
|
Sign up to set email alerts
|

The Face of Suffering Among Women With Breast Cancer—Being in a Field of Forces

Abstract: Through qualitative interviews, the suffering experiences of women with breast cancer and their significant others were disclosed. Seventeen women with different stages of breast cancer and 16 significant others from 4 different care cultures in Sweden and Finland participated. Five of the women had advanced metastatic breast cancer, and 12 had a localized disease. Mean age was 48 years. As a methodology, a team approach, inspired by the Vancouver School of Doing Phenomenology, was used. The findings elucidate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
72
0
11

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(89 citation statements)
references
References 10 publications
4
72
0
11
Order By: Relevance
“…These findings support and add to those of previous research, which has shown that isolation can be experienced at many different stages of the cancer journey (Arman, Rehnsfeldt, Lindholm & Hamrin, 2002), not least in the post-treatment phase (Halldorsdottir & Hamrin, 1996). One reason for this may be that cancer survivors often experience a sense of social stigma and can be seen as 'omens of hazard' and discouraged by society from expressing their feelings (McKenzie & Crouch, 2004).…”
Section: Isolationsupporting
confidence: 87%
“…These findings support and add to those of previous research, which has shown that isolation can be experienced at many different stages of the cancer journey (Arman, Rehnsfeldt, Lindholm & Hamrin, 2002), not least in the post-treatment phase (Halldorsdottir & Hamrin, 1996). One reason for this may be that cancer survivors often experience a sense of social stigma and can be seen as 'omens of hazard' and discouraged by society from expressing their feelings (McKenzie & Crouch, 2004).…”
Section: Isolationsupporting
confidence: 87%
“…탐구가 힘들며 환자들이 다른 방식으로 표현해내는 중요한 문 제들을 간과하기 쉽다 (Larsson et al, 2007) 암환자의 경험에 대한 질적 연구를 살펴보면 진행성 암환자 (Coyle, 2006;Tae, Cho, & Hong, 2003), 유방암 환자 (Arman, Rehnsfeldt, Lindholm, & Hamrin, 2002;Kooken, Haase, & Russell, 2007;Vargens & Bertero, 2007), 위암 환자 (Lee, 1996), 자가골수이식 암환자 (Jones & Chapman, 2000), 노인 암 환자 (Thome, Esbensen, Dykes, & Hallberg, 2004), 화학 요법 (Mitchell, 2007), 방사선요법 (Larsson et al, 2007), 수 술요법 (Kim, Park, Kim, & Kim, 2004), 의사소통 (Kvale, 2007;Papadopoulos & Lees, 2004) 등을 중심으로 연구되었 다. 그러나 많은 암환자들은 질환자체보다 현재를 살아나가는 데 초점을 맞추기를 원한다 (Kvale, 2007) …”
Section: 로써는 암환자의 독특한 경험이나 삶의 총체적인 상황에 대한unclassified
“…However, the participants in this study felt that appointments with the doctor were reassuring to know that clinically there were no problems detected and they did not discuss a need for psychological and emotional assessment. Arman et al (2002) discovered that women who experienced breast cancer found themselves in a situation that changed their lives, their perspectives on life, and their relationships. Nothing was now experienced as it had been prior to the diagnosis of breast cancer, and everything in their lives became centred on the event.…”
Section: The Findings Sample Characteristicsmentioning
confidence: 99%